Pengaruh Lingkungan Kerja dan Kepuasan Kerja Terhadap Kinerja Karyawan PT. Prima Putra Adiwahana - Plafianto J. Himpi; Ridolof W. Batilmurik; Chindy A. T. Maukaling (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This research aims to analyze the impact of the work environment and job satisfaction on employee performance at PT. Prima Putra Adiwahana, a car dealership. Employee performance is considered crucial as a determinant of the company's progress, and this study focuses on the role of the work environment and job satisfaction in achieving optimal results. The research method involves the use of a questionnaire distributed to all company employees. The measurement instruments include aspects such as organizational culture, interpersonal quality, resource availability for job satisfaction; positive work attitude, organizational commitment, and satisfaction with salary and compensation for the work environment; as well as work outcomes or output, work quality, innovation and creativity, and adherence to rules and policies for employee performance. Data analysis is conducted using descriptive statistics and Structural Equation Modeling (SEM) with SmartPLS version 3.0. The research results are expected to provide in-depth insights into the factors influencing employee performance at PT. Prima Putra Adiwahana and can be used as a basis for improvements and developments within the company.